Interdependence: a new model for the global approach to disability - Nathan Grills (Health for All Nations, 2015)
Disability affects over 1 billion people and the WHO estimates that over 80% of individuals with disability live in low and middle income countries, where access to health and social services to respond to disability are limited 1. Compounding this poverty is that medical and technological approaches to disability, however needed, are usually very expensive. Yet, much can be done at low cost to increase the wellbeing of people with disability, and the church and Christians need to take a lead. The WHO's definition of disability highlights the challenge to us in global health. It has been defined by the WHO as "the interaction between a person's impairments and the attitudinal and environmental barriers that hinder their full and effective participation in society on an equal basis with others" 2. This understanding of disability requires us to go beyond mere healing and towards inclusion in our response to chronic diseases and disability. This is known as the social model and requires societal attitudinal change and modification of disabling environments in order to facilitate those with disability to be included in our community and churches. These are good responses but the church needs to consider alternative models to those that are currently promoted which strive for independence as the ultimate endpoint. In this paper I introduce some disability-related articles in this issue and outline an approach that goes beyond the Social Model towards an Interdependence Model which I think is a more Biblical model of disability and one which we Christians and churches in global health should consider. This model would go beyond changing society to accommodate for people with disabilities towards acknowledging they play an important part in our community and indeed in our church. We need those people with disability to contribute, love and bless those with and without disabilities. And of course those with disability need the love, care and acceptance of those without disability. This is the society that is described in the Bible perhaps most clearly in 1 Corinthians 12:12-28. In verse 22 Paul states that those who are seemingly weaker are actually indispensable. When each part plays its role and depends on each other, we are a truly healthy, and a more biblical and better society. This approach would promote the wellbeing and spiritual health of those people with disability and when undertaken by a church would not necessarily entail a high monetary cost. Ultimately, it promotes the dignity of those with disability as created in God's image for His purposes.